PENGEMBANGAN ALAT WATER MONITOR PADA BUDIDAYA IKAN AIR TAWAR MENGGUNAKAN MIKROKONTROLER ARDUINO SEBAGAI SUMBER BELAJAR FISIKA - Sari, Maya; Riswanto, Riswanto; Prihandono, Eko (JURNAL FIRNAS, 2022)
Abstract: The purpose of this study was to determine the feasibility of the water monitor tool product, to determine the effectiveness of the product developed as a learning resource for students of SMK Negeri 2 Metro, to determine the user's response to the product developed. The development of this product can make it easier for fish farmers to monitor the pH and temperature of pond water and as a teacher learning supplement in practical activities at school. The product developed is a water monitor which is used to make it easier to monitor the pH and temperature of the water so that the fish care process becomes better and easier. The system for monitoring the pH and temperature of pool water is expected to be a system that can monitor the pH and temperature of the water and can condition it into the specified parameters. This research method uses the R&D (Research and development) method and uses the ADDIE model. Data collection instruments using data triangulation methods include three instruments, namely observation, interviews, and questionnaires. The data triangulation method is used by researchers to make it easier to draw conclusions. Based on the results of the analysis of the three instruments that have been triangulated, it proves that the results of the responses of teachers, students, and the community produce an average response of 84.97% and are in the very good category.Keywords: Cultivation, Practice, pH and temperature.